Tornar-se professor da EJA: um estudo priorizando a dimensão afetiva - Mollica, Andrea Jamil Paiva (2010)
This research main problems were to understand feelings and emotions of teachers (undergraduates student of Education or graduated in Education) working for the first time with Education for Youth and Adults (EJA) and to understand what causes that feelings and emotions. The purpose of this study was to identify teachers' needs regarding his/her undergraduate course or regarding the help that the school must provide in that period of his/her carreer. The Henry Wallon's theory was chosen because the present research gived priority to affectivity matters. The qualitative approach was used and, to collect the data, individual interviews were made with four beginner teachers based on reflexive modality. Transcription, tables and summaries of these interviews were elaborated to aid the data discussion analyses. The main results were: 1) EJA beginner teachers need co-workers' support to help in the job and they value the Coordinator Teacher's assistance, even teachers whose had work experience in different Education field. 2) it is necessary to think about changes in the Education undergraduates courses because specific training is indispensable to teach youth and adults students. 3) interviewee teachers value their career and they want to keep teaching despite all problems in the job. They understand that their own efforts are necessary to improve the education situation